Two-Echelon Repairable Item Inventory System with Limited Repair Capacity under Nonstationary Demands - LAU, Hoong Chuin (Institutional Knowledge at Singapore Management University, 2004)
We study a repairable item inventory system under limited repair capacity and nonstationary Poisson demands, motivated by corrective maintenance of military equipment. Our goal is to minimize the cost of both spare and repair resource allocation. We propose an efficient analytical model that combines optimization modeling and queuing theory.